The Influence of Au, Gd and I Nanoparticles on Radiation Dose Absorption during High Dose Rate Brachytherapy with 192Ir Source (Brazilian Journal of Radiation Sciences (BJRS), 2025)
The efficacy of high dose rate (HDR) brachytherapy for cervical cancer is often constrained by the high radiation exposure to the healthy tissues that surround the tumor consequently diminishing the therapeutic benefits of the technique. A promising approach to mitigate this challenge is the use of high atomic number (Z) nanoparticles, such as Gold nanoparticles (GNPs), Gadolinium nanoparticles (GdNPs) and Iodine nanoparticles (INPs), which act as radioation dose enhancers. This study evaluates the influence of GNPs, GdNPs and INPs nanoparticles on dose absorption during 192Ir HDR brachytherapy using Geant4 based Monte Carlo (G4MC) simulation. The study deployed nanoparticles of various concentrations ranging from 3 mg/g to 30 mg/g. It was found that the presence of these nanoparticles significantly increases the dose in the tumor with GNPs causing higher dose deposition to the tumor than it is the case for GdNPs and INPs. It was further observed that the Dose Enhancement Factor (DEF) depends on the concentration and type of the nanoparticles.  The maximum DEF was obtained at the concentration of 30 mg/g for each type of nanoparticle with the corresponding values being 1.82 for GNPs, 1.42 for GdNPs and 1.38 for INPs. These results indicate that incorporation of GNPs, GdNPs and INPs in HDR brachytherapy can enhance the efficacy of cancer tumor eradication. Hence, the use of GNPs during HDR brachytherapy at the concentration of 30 mg/g is recommended for effective cervical cancer treatment and management.